2022
DOI: 10.3390/antibiotics11030352
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Ceftriaxone-Loaded Cellulose Acetate and Polyvinyl Alcohol Nanofibers and Their Antibacterial Evaluation

Abstract: Nanotechnology provides solutions by combining the fields of textiles and medicine to prevent infectious microbial spread. Our study aimed to evaluate the antimicrobial activity of nanofiber sheets incorporated with a well-known antibiotic, ceftriaxone. It is a third-generation antibiotic that belongs to the cephalosporin group. Different percentages (0, 5%, 10%, 15%, and 20%; based on polymer wt%) of ceftriaxone were incorporated with a polymer such as polyvinyl alcohol (PVA) via electrospinning to fabricate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…Thereby, an increase in the swelling ratio with an increase in the pH of the buffer, due to de-protonation of the carboxylic group on SA, produced a strong swelling action by electrostatic forces of repulsion on the negatively charged group of SA and PVA. Our findings agree with those in the literature [ 41 , 42 , 43 ]. Additionally, the decrease in swelling ratio is due to the formation of the hydrogen bonding network of MMT with the polymers, which enhances the surface coarseness of films and closed the water penetration corridor resulting in a decrease in water compassion of the polymer films [ 42 ].…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…Thereby, an increase in the swelling ratio with an increase in the pH of the buffer, due to de-protonation of the carboxylic group on SA, produced a strong swelling action by electrostatic forces of repulsion on the negatively charged group of SA and PVA. Our findings agree with those in the literature [ 41 , 42 , 43 ]. Additionally, the decrease in swelling ratio is due to the formation of the hydrogen bonding network of MMT with the polymers, which enhances the surface coarseness of films and closed the water penetration corridor resulting in a decrease in water compassion of the polymer films [ 42 ].…”
Section: Resultssupporting
confidence: 94%
“…Figure 3 C,D showed large blocks; nanoclay has made small dot-like structures which are consistently dispersed in the formulation proving its high compatibility with the matrix. The presence of drug in the form of large-sized blocks or long rod-shaped crystals confirmed its crystalline structure, which was also revealed by previous studies [ 41 ].…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…It was observed that the diameter of the nanofiber patches increased with the loading of the drug. Other studies also support that the average diameter increases when the drug is loaded into the pure PVA nanofiber patches . Especially, a sharp increase was seen in the diameter of the PVA/GEL/CA/GEN nanofiber patches loaded with both types of drugs.…”
Section: Resultsmentioning
confidence: 65%